The Politics of Financial Development: Evidence from Trade Liberalization - BRAUN, MATIAS; RADDATZ, CLAUDIO (Journal of Finance, 2008)
ABSTRACT Incumbents in various industries have different incentives to promote or oppose financial development. Changes in the relative strength of promoter and opponent industries thus result in changes in the political equilibrium level of financial development. We conduct an event study using a sample of 41 countries that liberalized trade during 1970 to 2000, and show that the strengthening of promoter relative to opponent industries resulting from liberalization is a good predictor of subsequent financial development. The benefits of developing the financial system are insufficient for financial development, and rents in particular hands appear to be necessary to achieve it.